ANALISIS KANDUNGAN BORAKS SEBAGAI BORON PADA GENDAR YANG DIPRODUKSI OLEH INDUSTRI RUMAH TANGGA DI DAERAH AMBARAWA - sugiyono sugiyono; siti musinah; rukhanah rukhanah (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2009)
ABSTRACTGendar is a type of food produced by adding bleng, which is a chemical compound containing borax asboros. This research was intended to find out (1) the borax contents in the gendar taken from Ambarawa areas and(2) whether there were significant differences in borax levels contained in fresh gendar, dry gendar, gendar fried infresh vegetable oil and gendar fried in used vegetable oil.This was a non-experimental research with the data analyzed descriptively and analytically. The variablesmeasured were borax levels, acting is boros, contained in fresh gendar, dry gendar, gendar fried in fresh vegetableoil and gendar fried in used vegetable oil. The samples for this research were taken randomly from three householdindustried of gendar in Ambarawa areas. The contents of borax were measured using spectrophotometri UV-Vis.The analyses on the borax content in the four types of gendars (fresh gendar, dry gendar, gendar fried in freshvegetable oil and gendar fried in used vegetable oil) used Kruskall-Wallis non-parametric statistical tests followedby Mann-Whitney tests.The analyses showed that all of the four types of gendars really contained borax, as boros, but in diffirentlevels among the diffirent gendars borax contents in the four different gendars taken from Bandungan andSumowono had significant values 0,182 and 0,643 respectively (P > 0,05), contents in the four different gendarstaken from Ambarawa areas also had a significant value of 0,004 (P < 0,05), meaning also that there werestatistically significant differences in the borax contents.Keywords : Borax, Gendar, Spectrophotometri UV-Vis.